Upaya Pembinaan Menuju UMKM Digital Era 5.0 Desa Napal Licin: Upaya Pembinaan Mneuju UMKM Digital Era 5.0 - Alaksari, Sirajudin; Anisah, Anisah; Saskia, Arna; Fauzani, Fauzani (Yayasan Rahmatan Fidunya Wal Akhirah, 2025)
Abstract : The development of technology in Indonesia is currently inevitable along with the advancement of science. This development certainly has various impacts, both negative and positive. One of the good impacts is the use of digital technology in the economic sector, especially on the sales or marketing side using digital media. Technological advances encourage micro, small and medium enterprises (MSMEs) to utilize digital platforms in selling and marketing their products. Currently, various social media applications can be used to expand promotional networks. Digital marketing not only expands the reach of promotion but also makes it easier for MSMEs to monitor consumer needs and provide convenience for consumers to obtain product information. Napal Licin Village, North Musi Rawas Regency, South Sumatra is one of the villages that has a large and varied number of MSMEs, so the development of MSMEs really needs to be improved. Therefore, the use of digitalization is very important in the development of MSMEs in Napal Licin Village. The purpose of implementing this activity is to empower MSME actors in innovating and utilizing digitalization as a marketing medium for their businesses or products. The methods used in this activity are socialization, discussion, questions and answers, practice, mentoring and evaluation. Based on the results of the activity, it can be seen that all stages of the activity can be carried out well and smoothly, the activity runs conducively, effectively and efficiently as evidenced by the majority actively participating and being enthusiastic in following the series of socialization activities. Participants are also actively involved in the process of practicing or mentoring the creation of advertising designs as a promotional media that is carried out. The level of participant satisfaction in participating in the activity is indicated by a percentage of 85% of participants feeling very satisfied with the socialization and materials provided, while 5% of participants feel satisfied and 10% feel that the socialization carried out is ordinary.